ANALISIS INOVASI DISRUPTIF PADA IKM MAKANAN DI KOTA MALANG - Devan Christian Sugiarto (Ma Chung Press, 2018)
The existence of ASEAN Economic Community exposes Indonesia to global competition. SMI as an economic power needs to have long-term competitiveness in order to survive in the competition. Currently there is one kind of innovation that matches with SMI, that is disruptive innovation. Disruptive innovations in concept are often initiated by small industries, by taking a less profitable market or creating a new market. This study aims to explore information about the process of emergence disruptive innovation and driving factors as well as inhibiting factor to emergence disruptive innovation. The approach used is through qualitative research so that researchers can know clearly the processes and factors that influence the emergence of disruptive innovation. This study found that the emergence of disruptive innovation in SMI food in Malang is not too complicated. This is the processes experienced by the three SMI foods that studied by researcher: (1) Identification of Opportunities, (2) Fact Finding, (3) Idea Development, (4) Budget Planning, (5) Implementation. While the driving factors found by the researcher are as follows: (1) Market Opportunity, (2) Consumer, (3) Competition, (4) Information, (5) Personal Motivation, and (6) Labor. For the inhibiting factors are: (1) Capital, (2) Knowledge, (3) Mindset, (4) Legality and (5) Supplier.